Bacterial ecology in Amazonian soils under deforestation and agricultural management - Navarrete, Acacio Aparecido (2013)
This thesis assessed effects of Amazonian deforestation on artificial association networks of bacteria to bacteria and to abiotic soil factors and networks based on categories of bacterial functions and abiotic soil factors, and sought a better insight into community of Acidobacteria in Amazon soils under agricultural management of soybean based on culture-dependent and molecular approaches. Bacterial community was studied based on next-generation sequencing technologies (Roche GS FLX Titanium and Illumina HiSeq 2000 platforms), quantitative real-time PCR, fingerprinting technique and basic procedures for bacteria culture. The general objective of this thesis was achieved by development of three different studies. The Study 1 analyzed the total bacterial community based on 16S ribosomal DNA pyrotag (425 thousand sequences), shotgun metagenomics (266 million sequences) and environmental parameters from soil samples collected in three real replicate of intact Amazon rainforest and adjacent deforested site after 2-4 months of forest clearing and burning in the Brazilian Amazon. This study showed that deforestation of Amazon forest soils led to a consistent decline in the abundance of Verrucomicrobia and alterations in verrucomicrobial community structure, and simplified association networks among different bacterial taxonomic groups and abiotic soil factors. In order to adapt to this condition function-based associations network were enhanced, indicating a higher degree of risk spreading for the maintenance of soil functioning. The Study 2, in turn, correlated relative abundance of Acidobacteria subgroups - based on approximately 33 thousand sequences of acidobacterial 16S rRNA genes - and abiotic soil factors, and showed differential response of Acidobacteria subgroups to abiotic soil factors in Amazon forest soils into soybean croplands. This study opened the possibilites to explore acidobacterial subgroups as early-warning bio-indicators of agricultural soil management effects in the Amazon area. Lastly, the Study 3 reported the culturability and molecular detection of Acidobacteria subgroups 1 and 3 concomitantly to other bacterial groups from Amazon soils on enriched culture medium with carbon source and incubated for relatively long period in hypoxic atmosphere (2% O2 [vol/vol], 2% CO2 [vol/vol] and 96% N2 [vol/vol]), and validated the combination of traditional procedures for bacteria culture and molecular techniques for recover and detection of Acidobacteria from Amazon soils